Bilateral Intracavernous Carotid Artery Aneurysms Presenting as Diplopia in a Young Patient - Nikolaos Kopsachilis; Maria Pefkianaki; Gianluca Carifi; Ioannis Lialias (Case Reports in Medicine)
Introduction. Bilateral intracavernous carotid artery aneurysms (ICAAs) are extremely rare and difficult to treat. Case Report. A 26-year-old female presented in our clinic with acute diplopia due to oculomotor nerve palsy on the left side. Magnetic resonance imaging of the brain showed two heterogeneously enhanced masses indicating bilateral ICAA. An endovascular coil embolization was performed on the left side successfully, resulting in resolution of her symptoms. Conclusion. Thorough systemic evaluation in young patients with diplopia can reveal life-threatening underlying pathology and prevent major complications.